Case Report: The intersection of psychiatry and medicine: diagnostic and ethical insights from case studies - Monaco, Francesco; Vignapiano, Annarita; D’Angelo, Martina; Raffone, Fabiola; Di Stefano, Valeria; Boccia, Antonella; Longobardi, Anna; Gruttola, Benedetta Di; Fornaro, Michele; Corrivetti, Giulio; Martino, Iolanda; Steardo, Luca; et al. (Frontiers in Psychiatry, 2025)
The intersection of psychiatry and medicine presents unique diagnostic and ethical challenges, particularly for conditions involving significant brain-body interactions, such as psychosomatic, somatopsychic, and complex systemic disorders. This article explores the historical and contemporary issues in diagnosing such conditions, emphasizing the fragmentation of medical and psychiatric knowledge, biases in clinical guidelines, and the mismanagement of complex illnesses. Diagnostic errors often arise from insufficient integration between general medicine and psychiatry, compounded by the reliance on population-based guidelines that neglect individual patient needs. Misclassification of conditions like myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), Lyme disease, and fibromyalgia as psychosomatic or psychogenic has led to stigmatization and delayed care. While these conditions are referenced as emblematic examples of misclassified and poorly understood disorders, the five clinical cases discussed in this article do not directly illustrate these diseases. Instead, they exemplify shared diagnostic and ethical dilemmas at the medicine–psychiatry interface, including uncertainty, fragmentation, and the risk of epistemic injustice. The article critically examines terms like medically unexplained symptoms and functional disorders, highlighting their limitations and potential for misuse. Case examples underscore the consequences of diagnostic inaccuracies and the urgent need for improved approaches. Ethical considerations are also explored, emphasizing respecting patient experiences, promoting individualized care, and acknowledging the inherent uncertainties in medical diagnosis. Advances in technologies such as brain imaging and molecular diagnostics offer hope for bridging the gap between psychiatry and medicine, enabling more accurate assessments and better patient outcomes. The article concludes by advocating comprehensive training at the medicine-psychiatry interface and a patient-centered approach that integrates clinical observation, research insights, and a nuanced understanding of mind-body dynamics.